2021
DOI: 10.3390/antiox10060919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Quinone Oxidoreductase WrbA on Escherichia coli Biofilm Formation and Oxidative Stress

Abstract: The effects of natural compounds on biofilm formation have been extensively studied, with the goal of identifying biofilm formation antagonists at sub-lethal concentrations. Salicylic and cinnamic acids are some examples of these compounds that interact with the quinone oxidoreductase WrbA, a potential biofilm modulator and an antibiofilm compound biomarker. However, WrbA’s role in biofilm development is still poorly understood. To investigate the key roles of WrbA in biofilm maturation and oxidative stress, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 106 publications
(133 reference statements)
0
29
0
Order By: Relevance
“…To evaluate whether AlgR regulates RNR expression under oxidative stress conditions during infection, we measured RNR induction in a continuous biofilm, which can simulate an infection-like situation ( 24 ). Other studies have already measured ROS in biofilms and have shown the importance of this growth condition during infection ( 25 ). In our experiments, we used a continuous flow biofilm to measure nrdJ and nrdA expression under oxidizing conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether AlgR regulates RNR expression under oxidative stress conditions during infection, we measured RNR induction in a continuous biofilm, which can simulate an infection-like situation ( 24 ). Other studies have already measured ROS in biofilms and have shown the importance of this growth condition during infection ( 25 ). In our experiments, we used a continuous flow biofilm to measure nrdJ and nrdA expression under oxidizing conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Later, using a similar pull-down approach, WrbA was identified as the protein interacting with the antibiofilm molecule T315, a phenyl-pyrazole analog that targets the etiological agent of typhoid fever, Salmonella enterica serovar Typhi [ 24 ]. SA, as well as the ZA-analogous compound cinnamic acid (CA), exhibited an antibiofilm effect at non-lethal concentrations [ 21 , 23 ] and demonstrated inhibition of the NADH-dependent oxidoreductase function of E. coli WrbA [ 25 , 26 ]. A WrbA-deprived (∆ wrb A) mutant strain of E. coli was used to prove the involvement of WrbA in biofilm formation, which occurs through a mechanism dependent on the ROS level [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…SA, as well as the ZA-analogous compound cinnamic acid (CA), exhibited an antibiofilm effect at non-lethal concentrations [ 21 , 23 ] and demonstrated inhibition of the NADH-dependent oxidoreductase function of E. coli WrbA [ 25 , 26 ]. A WrbA-deprived (∆ wrb A) mutant strain of E. coli was used to prove the involvement of WrbA in biofilm formation, which occurs through a mechanism dependent on the ROS level [ 25 ]. The lack of WrbA function resulted in a ROS-sensitive phenotype characterized by a reduced number of biofilm-dwelling cells, decreased biofilm thickness, lower matrix polysaccharide content, and reduced tolerance to hydrogen peroxide [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, salicylic acid, the active component of aspirin, has been proved to interact with the quinone oxidoreductase WrbA, reducing Escherichia coli biofilm through a mechanism that depends on ROS [ 5 , 7 ]. N-acetylcysteine is used as mucolytic drug and it is applied on a broad range of pathologies with the primary role of antioxidant agent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%